An Eye-Opening Experience with Visual Impairment Students’ environment in Brunei Darussalam - Sheikh Haji Khalid, Sheikh Mohamed Izzat Bin; Abdul Latif, Siti Norhedayah; Haji Zailani, Fifi Faulina (International Journal of Social Learning (IJSL), 2022)
This paper aims to explore the experiences of students with visual impairment (VI) within their built school environment. A qualitative case study of four students with VI from three secondary government schools were interviewed following site observations of their schools. The study found that the students with VI do face anxiety towards their built school environment alongside the barriers they faced which can be thematically categorized into physical barriers, auditory barriers and lighting barriers. The study also revealed that many aspects of the school buildings and environment presented challenges and are intimidating to maneuver for VI students. The study has implications in expanding the field of study into Universal Design within Brunei Darussalam where future research can approach UD and it’s aspects in depth. Finally, the country had started dialogue regarding accessibility and its significance in the country’s National Vision Plan 2035 and the study hopes to bring insight into the types of barriers the built environment can have on students with VI and signal future development projects forward.